Widowhood Impairs Emotional Cognition Among Elderly - Bi, Taiyong; Kou, Hui; Kong, Yanshu; Shao, Boyao (Frontiers in Aging Neuroscience, 2022)
Background: The negative impacts of spousal bereavement on the emotional health of the elderly (e.g., depression and anxiety) have been revealed. However, whether widowhood impairs emotional cognition among the elderly is little known. The purpose of the present study is to reveal the emotional cognitive deficits among the widowed elderly. Methods: In the present study, we recruited 44 widowed elderly (WE) and 44 elder couples (non-widowed elderly, NWE), and examined their emotional cognition including attention and visual working memory which were measured by the visual search task and delayed-match-to-sample task respectively. Three kinds of emotional faces (sad, angry, happy) were adopted as the attentional or mnemonic targets. Results: It revealed that WE had a general deficit in search efficiency across emotional types, while they showed mnemonic deficits in negative faces but not positive faces. Furthermore, modeling analysis revealed that the level of depression or state-anxiety of the elderly moderated the effects of widowhood on the deficits of mnemonic processing, i.e., the deficits were only evident among WE with the high level of depression or state-anxiety. Conclusion: These findings reveal the attentional deficits in sad, angry, and happy faces, and the mnemonic deficits in sad and angry faces among elderly who suffer from widowhood, and point out the important role of emotional problems such as depression and state-anxiety in modulating these emotional cognitive deficits.